PÓS-TRATAMENTO DE EFLUENTE SECUNDÁRIO DE INDÚSTRIA DE PAPEL POR ULTRAFILTRAÇÃO, UV/ H2O2 E FOTO-FENTON - Neves, Ludmila Carvalho (2017)
It was investigated if the packing density of the ultrafiltration module affects the paper mill wastewater treatment, it was also evaluated if the complete factorial and fractional factorial experimental designs are efficient statistical techniques to found the optimum operational UV/H2O2 and photo-Fenton in the treatment of the wastewater study, and finally a comparative study of effluent phytoxicity was performed before and after UV / H2O2 and photo-Fenton post-treatments. There is no significant difference between the quality of the permeates produced by the modules with different packing densities, but, because it provides greater productivity to the treatment, the module with the highest packing density is the most viable for the treatment. Both the complete factorial arrangement and the fractional factorial arrangement are efficient techniques to measure the optimum operational of the studied oxidative processes, but due to their economic advantages the fractional factorial arrangement is the most attractive. The raw effluent was considered to be very toxic to the test organisms used, but there was a significant reduction of toxicity after post-treatment UV/H2O2 and photo-Fenton.